A systematic review and meta-analyses of the relationship between glutathione S-transferase gene polymorphisms and renal cell carcinoma susceptibility - Zhiqing Zhong; Hongyan Li; Hongzhen Zhong; Tianbiao Zhou; Weiji Xie; Zhijun Lin (BMC, 2018)
Abstract Background Association of GSTM1- and GSTT1-null genotypes, GSTP1 A/G gene polymorphism with renal cell carcinoma (RCC) susceptibility was detected, and the relationship between the GSTM1/GSTT1-null genotype and clinical TNM stages of RCC was assessed, using meta-analysis method. Methods Association investigations according to eligibility criteria were searched and identified from the databases of Cochrane Library, PubMed, and Embase from establishment time of databases to July 1, 2017, and eligible reports were analyzed by meta-analysis. 95% confidence intervals (CI) were also detected, and odds ratios (OR) was used to express the results for dichotomous data. Results This meta-analysis indicated that there was no an association between GSTM1-null genotype, GSTT1-null genotype, GSTP1 A/G gene polymorphism and RCC risk in the overall population of Caucasians or Asians. The dual GSTM1-GSTT1-null genotype was also not associated with RCC in the overall population of Caucasians. Interestingly, there was an association between the dual GSTM1-GSTT1-null genotype and the susceptibility of RCC in Asians. Relationship of the GSTM1-null genotype with clinical TNM stage of RCC was not observed in the overall population of Asians or Caucasians. In this meta-analysis, no association between the GSTT1-null genotype and clinical TNM stage of RCC was observed in Caucasians or Asians. Interestingly, GSTT1-null genotype was detected to be associated with the clinical TNM stages in patients with RCC in the overall population. Conclusion The dual GSTM1-GSTT1-null genotype is detected to be associated with the onset of RCC in Asians, and there is an association between the GSTT1-null genotype and the clinical TNM stages in patients with RCC in the overall population.